Designing a Computer Network in Building a Smart School with Case Study of SMA Negeri 1 Kediri - Wijaya, Ni Putu Ega Meiliana; Ari Mogi, I Komang (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2020)
Smart school is a technology-based school concept used in the teaching and learning process in the classroom. The use of educational technology includes an integrated system that assists the educational community in carrying out their respective functions with the aim of developing the potential of students. The use of technology in the field of education is expected to help and facilitate students and schools in conducting learning so that technology is able to facilitate and solve problems in learning. In building smart schools, it is also necessary to design technology developed in technology. The concept of network development that will be used is to use the Top-Down method and the topology used is to use ring topology and star topology. With the development of smart schools, it is expected that education using technology will continue to develop.